Association between composite dietary antioxidant index and Epstein–Barr virus infection in children aged 6–19 years in the United States: from the national health and nutrition examination survey 2007–2010 - Cheng, Wei; Wang, Yunfei; Ding, Nan; Xie, Rutao (Frontiers in Nutrition, 2025)
ObjectiveEpstein-Barr virus (EBV) is a globally prevalent herpes virus associated with multiple diseases. Oxidative stress is closely related to EBV infection, latency, reactivation, and transformation. Antioxidant diet protects against EBV infection. Composite Dietary Antioxidant Index (CDAI), serving as a key measure of antioxidant intake, is a summary score of six dietary antioxidants, including vitamins A, C, and E, carotenoid, selenium, and zinc. Despite this, the association between CDAI and EBV infection remains uncertain.MethodsThe aim of the study was to evaluate the association between CDAI and EBV infection using cross-sectional data from 3,318 children aged 6–19 years who participated in the American National Health and Nutrition Examination Survey between 2007 and 2010. Data on EBV results, CDAI, and several other essential variables were analyzed.ResultsCompared with that of individuals in Q3 (−1.627–−0.2727) in the multivariate weighted logistic regression model with full adjustment for confounding variables, the adjusted odds ratio (OR) for CDAI and EBV infection in those in Q1 (−6.613 − −2.9157), Q2 (−2.9158–−1.626), Q4 (−0.2728–1.7601), and Q5 (1.7602–21.419) was 1.41 (95% CI: 1.01–1.96, p = 0.043), 1.10 (95% CI: 0.84–1.45, p = 0.447), 1.14 (95% CI: 0.86–1.51, p = 0.343), and 1.41 (95% CI: 1.01–1.98, p = 0.044), respectively. The association between CDAI and EBV infection showed a U-shaped curve (non-linear; p = 0.002). The OR of reducing EBV infection was 0.882 (95% CI: 0.792–0.982, p = 0.025) in participants with a CDAI of ≤ − 0.81. The OR of developing EBV infection was 1.055 (95% CI: 1.000–1.114, p = 0.050) in participants with a CDAI of > − 0.81.ConclusionOur results indicated that the association between CDAI and EBV infection in U.S. adolescents follows a U-shaped curve, with an inflection point around –0.81.This suggests that an antioxidant-rich diet in some amount could help reduce the risk of EBV infection. Future prospective and experimental studies are needed to confirm causality and clarify the exact mechanism concerning antioxidant diets with EBV infection.